Greening competitiveness for hotels and restaurants. Issue 3 (21st August 2017) - Iraldo, Fabio; Testa, Francesco; Lanzini, Pietro; Battaglia, Massimo
Abstract : Purpose: The purpose of this paper is to present the results of a survey-based study performed on Italian SMEs in the "hotel, restaurant, café" (HORECA) sector, aimed at investigating the relationship between pro-environmental strategies and competitiveness and how such strategies can be exploited to outperform competitors. Design/methodology/approach: The survey involved 317 Italian SMEs. Regression models have been developed to analyze the causal relationship between three dimensions of competitiveness (competitive advantage over competitors, customer satisfaction and employees' motivation), and environmental practices that can be adopted by HORECA SMEs. Findings: Top management commitment emerges as a key driver of competitiveness, confirming the strategic relevance of a sound approach to sustainability also in SMEs operating in the tourism sector. Moreover, actions aimed at investing in green food products (e.g. organic food) and awareness campaigns emerge as strong predictors of good business performance. Finally, at managerial level, entrepreneurs and owners evaluate the implementation of internal sustainability monitoring systems as a relevant support to increase their competitive performance. Research limitations/implications: Since the results are limited to Italian HORECA businesses, a cross-country comparison could represent a potential improvement of the research. Moreover, since the sector is characterized by the predominance of small and micro firms, specific attention should be devoted to the role played by entrepreneurs' personal values in shaping business strategies. Originality/value: The paper contributes to the ongoing debate on the relationship between SMEs in the tourism sector and the environmental dimension analyzing the link between the adoption of "green" practices and the competitive performance. The results suggest that customer involvement represents an essential pre-requisite to turn sustainability into an opportunity of market distinctiveness and stress the strategic role of the implementation of performance monitoring systems.